A case of chronic eosinophilic pneumonia associated with rheumatoid arthritis in glucocorticoid-free remission with JAK inhibitor: A case report. Issue 13 (31st March 2023) - Yamane, Takashi; Hashiramoto, Akira
Abstract : Rationale: Chronic eosinophilic pneumonia (CEP) presents eosinophil infiltrations in the lung due to allergic reactions. Most CEP patients continue to take glucocorticoids, and their prolonged use induces various side effects. In this case report, based on the efficacy of baricitinib in patients with rheumatoid arthritis (RA) and CEP, we aimed to show that the administration of Janus kinase (JAK) inhibitors, when RA is complicated by an allergic disease, can stabilize the disease state and help avoid the adverse effects of long-term systemic glucocorticoid administration. Patients concerns: A 56-year-old woman developed RA at the age of 19 years. Treatment of the arthritis was initiated, but the joint destruction had progressed. At the age of 42, she developed eosinophilic pneumonia, which was relieved by glucocorticoid therapy. Since then, maintenance therapy has been continued with the diagnosis of CEP. She was treated with concomitant tacrolimus for persistent arthritis, and the prednisolone (PSL) dose was reduced to 3 mg/day after 10 years. However, around this time, an increase in peripheral blood eosinophil counts and respiratory symptoms was observed. Diagnosis: The peripheral blood eosinophil count was 4000/µL and computed tomography revealed multiple ground-glass opacities in the peripheral lung fields. As interstitial pneumonia due to infection or other causes was ruled out, CEP relapse was diagnosed. Interventions: Pneumonia rapidly recovered when the PSL dose was increased to 15 mg/day, and asymptomatic eosinophilic infiltrates reappeared in the lung field along with a relapse of arthritis when the PSL dose was reduced to 5 mg/day. Concomitant use of methotrexate and baricitinib has been introduced to suppress allergic reactions to pneumonia. Outcomes: After starting combination therapy with baricitinib and methotrexate, both arthritis and eosinophilia improved, and glucocorticoid-free remission was achieved. Lessons: Recently, inhibition of IL-5 signaling via JAK2 has been reported to be effective in bronchial asthma and atopic dermatitis. Although complications of RA and CEP are not common, the actions of baricitinib are useful not only in arthritis but also in allergic diseases. The efficacy of some JAK inhibitors should be actively tested in patients with RA and these complications.